The Influence of Parenting Styles and Parental Attitudes on The Behavioral Development of Children Aged 3- 5 Years - Mudlikah, Siti (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2024)
Developmental abnormalities in children can occur as a result of parental inattention and attitudes. The purpose of this study is to understand better the association between parenting methods and parental attitudes and the conduct of children aged three to five. The research method is descriptive-analytical, with a cross-sectional approach. TKM NU 166 Nahdlatul Ummah Goloka Kanjeng Sepuh Gresik is home to 34 parents with children aged 3-5 years. Purposive sampling was utilized, with 30 parents as the sample size. Questionnaires were used to collect data on parenting techniques, parental views, and children's conduct. Observation checklists were also used. Data were processed using frequency distribution tables and examined using the Lamda statistical test. The outcomes of the data analysis were triangulated using interviews, observations, and documentation. The study found that 11 children (84.6percent) with democratic parenting exhibited prosocial behavior, but authoritarian and permissive parenting styles were linked to antisocial behavior. All children (100percent) of parents with negative attitudes engaged in antisocial behavior. The conclusion is that parenting techniques and parental attitudes influence children's conduct.